Nicotinamide inhibits melanoma in vitro and in vivo - Scatozza, Francesca (J Exp Clin Cancer Res, 2020)
BACKGROUND: Even though new therapies are available against melanoma, novel approaches are needed to overcome resistance and high-toxicity issues. In the present study the anti-melanoma activity of Nicotinamide (NAM), the amide form of Niacin, was assessed in vitro and in vivo. METHODS: Human (A375, SK-MEL-28) and mouse (B16-F10) melanoma cell lines were used for in vitro investigations. Viability, cell-death, cell-cycle distribution, apoptosis, Nicotinamide Adenine Dinucleotide(+) (NAD(+)), Adenosine Triphosphate (ATP), and Reactive Oxygen Species (ROS) levels were measured after NAM treatment. NAM anti-SIRT2 activity was tested in vitro; SIRT2 expression level was investigated by in silico transcriptomic analyses. Melanoma growth in vivo was measured in thirty-five C57BL/6 mice injected subcutaneously with B16-F10 melanoma cells and treated intraperitoneally with NAM. Interferon (IFN)-γ-secreting murine cells were counted with ELISPOT assay. Cytokine/chemokine plasmatic levels were measured by xMAP technology. Niacin receptors expression in human melanoma samples was also investigated by in silico transcriptomic analyses. RESULTS: NAM reduced up to 90% melanoma cell number and induced: i) accumulation in G1-phase (40% increase), ii) reduction in S- and G2-phase (about 50% decrease), iii) a 10-fold increase of cell-death and 2.5-fold increase of apoptosis in sub-G1 phase, iv) a significant increase of NAD(+), ATP, and ROS levels, v) a strong inhibition of SIRT2 activity in vitro. NAM significantly delayed tumor growth in vivo (p ≤ 0.0005) and improved survival of melanoma-bearing mice (p ≤ 0.0001). About 3-fold increase (p ≤ 0.05) of Interferon-gamma (IFN-γ) producing cells was observed in NAM treated mice. The plasmatic expression levels of 6 cytokines (namely: Interleukin 5 (IL-5), Eotaxin, Interleukin 12 (p40) (IL12(p40)), Interleukin 3 (IL-3), Interleukin 10 (IL-10) and Regulated on Activation Normal T Expressed and Secreted (RANTES) were significantly changed in the blood of NAM treated mice, suggesting a key role of the immune response. The observed inhibitory effect of NAM on SIRT2 enzymatic activity confirmed previous evidence; we show here that SIRT2 expression is significantly increased in melanoma and inversely related to melanoma-patients survival. Finally, we show for the first time that the expression levels of Niacin receptors HCAR2 and HCAR3 is almost abolished in human melanoma samples. CONCLUSION: NAM shows a relevant anti-melanoma activity in vitro and in vivo and is a suitable candidate for further clinical investigations.